2019
DOI: 10.1292/jvms.19-0059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of <i>in vitro</i> neurotoxicity of methylmercury, mercury, cadmium, and hydrogen peroxide on SH-SY5Y cells

Abstract: Mercury (Hg) and cadmium (Cd) are the major toxic heavy metals and are known to induce neurotoxicity. Although many studies have shown that several heavy metals have neurotoxic effects, the cellular and molecular mechanisms thereof are still not clear. Oxidative stress is reported to be a common and important mechanism in cytotoxicity induced by heavy metals. However, the assays for identifying toxic mechanisms were not performed under the same experimental conditions, making it difficult to compare toxic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…We first conducted an MTT assay to determine the dose–response of the cytotoxicity of MeHg in human neuroblastoma SH-SY5Y cells, applying the MeHg concentrations of 1–10 µM for 24 h. The viability of the cells treated with 3 µM MeHg was reduced to approximately 40% compared to the non-treated cells, and 10 µM MeHg significantly reduced the cell viability ( Figure 1 A). These results are consistent with previous findings in SH-SY5Y cells [ 14 , 15 ]. We next investigated the time–response of the cell viability by treatment with 3 µM MeHg for 0–24 h. The exposure of the cells with MeHg for up to 2 h did not affect the cell viability, and after 2 h the cell viability declined in a time-dependent manner ( Figure 1 B).…”
Section: Resultssupporting
confidence: 94%
“…We first conducted an MTT assay to determine the dose–response of the cytotoxicity of MeHg in human neuroblastoma SH-SY5Y cells, applying the MeHg concentrations of 1–10 µM for 24 h. The viability of the cells treated with 3 µM MeHg was reduced to approximately 40% compared to the non-treated cells, and 10 µM MeHg significantly reduced the cell viability ( Figure 1 A). These results are consistent with previous findings in SH-SY5Y cells [ 14 , 15 ]. We next investigated the time–response of the cell viability by treatment with 3 µM MeHg for 0–24 h. The exposure of the cells with MeHg for up to 2 h did not affect the cell viability, and after 2 h the cell viability declined in a time-dependent manner ( Figure 1 B).…”
Section: Resultssupporting
confidence: 94%
“…The present results corroborate the previous results which demonstrated that exposure to mercury stimulated the generation of ROS. Our results agree with further studies 22,23 . the combination of Hg and the P. atlantica extract in our study showed a reduction in TBARS levels in the brain.…”
Section: Discussionsupporting
confidence: 94%
“…The results here presented show a different cytotoxic response of HepG2 and SH-SY5Y that has equally been observed by other authors for TiO 2 NPs [ 47 ], CeO 2 NPs [ 48 ], As and Hg [ 49 ], with the neural cell line being more sensitive than HepG2 in all cases, after 24 h exposure. The same authors also observed a dose-dependent cytotoxic effect as observed in this study.…”
Section: Discussionsupporting
confidence: 81%